Smart Infusion Digitalization Based on IoT, Long-Range Communication, and Cloud - Ananta, Adam; Nasir, Muhammad; Erdiansyah, Umri (Journal of Artificial Intelligence and Software Engineering, 2024)
Currently, the monitoring of infusion fluids is performed by periodically checking each patient, regardless of whether there is an obstruction or not. To address this challenge, a system based on the Internet of Things (IoT), Long Range (LoRa) at a 2.4 GHz frequency, and Cloud technology, known as the digital smart infusion system, has been developed. This system aims to enhance the efficiency and safety of infusion fluid delivery, facilitate real-time monitoring by nurses, and provide accurate and up-to-date data. The testing results indicate that the implementation of the MQTT protocol in this system yields positive outcomes, with delay times varying between 42 ms (5 minutes), 84.3 ms (10 minutes), and 73.8 ms (15 minutes), along with very low packet loss rates of 0.03% at 5 minutes, 0.02% at 10 minutes, and 0.01% at 15 minutes. Additionally, the system's throughput remains stable, with values of 92.6 Kbps at 5 minutes, 83.8 Kbps at 10 minutes, and 86.2 Kbps at 15 minutes. In tests of LoRa without obstructions, packet loss percentages remain low up to a distance of 10 meters, with a value of 0%, but then increase to 68.29% at 25 meters. Tests with obstructions show a more drastic decline in signal quality, with packet loss reaching 6.98% at 5 meters and increasing to 70.97% at 25 meters.